Social Upbringing and Morality Based on Gnostic Teachings in Sa’eb’s Poems - Falahatkhah, Farhad; Najafi, Azizeh (Journal of History Culture and Art Research, 2017)
Humans’ social rearing within the context of the communities as highlighted in the Persian Gnosticism is closely connected to lenience, tolerance, and laxity, patience and forbearance, affection and anger avoidance. It is a fairly extended discussion which has drawn the attention in Persian literature and many of well-known poets have dealt with making statements in this regard with optimum use of terseness, aestheticism, and coherence. Sa’eb is among the poets who, based on mankind’s value, importance and veneration, have dealt with the survey of one of the most fundamental humans’ needs to wit the way humans are reared socially and he is well aware that real tranquility in a social level depends on guarding such values and moral behaviors as affection, altruism, forbearance etc. These are the topics most abundantly mentioned in Gnosticism. In Gnostic terms, upbringing is an introduction to reaching to cognizance and Sa’eb has well-discerned this very issue.